2001
DOI: 10.1128/jcm.39.8.2987-2990.2001
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the rpoB Gene of Multidrug-Resistant Mycobacterium tuberculosis Clinical Isolates from India

Abstract: Mutations in the 81-bp rifampin resistance-determining region (RRDR) of the rpoB gene were analyzed by DNA sequencing of 50 Mycobacterium tuberculosis clinical isolates (44 resistant and 6 sensitive) from various parts of India. Fifty-three mutations of 18 different kinds, 17 point mutations and one deletion, were observed in 43 of 44 resistant isolates. Three novel mutations and three new alleles within the RRDR, along with two novel mutations outside the RRDR, are reported in this study.Tuberculosis (TB), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
100
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 19 publications
14
100
1
1
Order By: Relevance
“…The mechanism of resistance to RIF involves missense mutations, small deletions or insertions in the rpoB gene encoding the b-subunit of RNA polymerase. Studies from diverse countries have shown that 95-96 % of all RIFresistant isolates have mutations within an 81 bp 'core region' of rpoB (Bártfai et al, 2001;Cavusoglu et al, 2002;Herrera et al, 2003;Mani et al, 2001;Telenti et al, 1993;Yue et al, 2003). In contrast, but perhaps not unexpectedly given its highly complex mechanism of action, the mutations causing INH resistance are located in more than three genes and regions (Barry et al, 1998;Slayden & Barry, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of resistance to RIF involves missense mutations, small deletions or insertions in the rpoB gene encoding the b-subunit of RNA polymerase. Studies from diverse countries have shown that 95-96 % of all RIFresistant isolates have mutations within an 81 bp 'core region' of rpoB (Bártfai et al, 2001;Cavusoglu et al, 2002;Herrera et al, 2003;Mani et al, 2001;Telenti et al, 1993;Yue et al, 2003). In contrast, but perhaps not unexpectedly given its highly complex mechanism of action, the mutations causing INH resistance are located in more than three genes and regions (Barry et al, 1998;Slayden & Barry, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Rifampicin resistance is of particular epidemiological importance, since it represents a valuable surrogate marker for multidrug resistant (MDR) tuberculosis strains as more than 90% of rifampicin resistant isolates are also isoniazid resistant [4,5]. Rifampicin interferes with transcription by binding to the beta subunit of DNA-dependent RNA polymerase.…”
Section: Introductionmentioning
confidence: 99%
“…(Mboowa et al, 2014). Mani et al, reported that the codons most commonly involved in these mutations were 531 (53%) and 526 (19%) in a study from South India (Mani et al, 2001). The resistant mutants isolated more frequently in clinical practice have higher mean relative fitness and their prevalence depend on their ability to survive (Billington et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…While, Singhal et al, found 6 strains (6/366) with more than one mutation (Singhal et al, 2015). Probably, mutations continue to arise due to the ability of MTB to adapt to drug exposure (Mani et al, 2001). The results were statically analyzed (p<0.0005).…”
Section: Resultsmentioning
confidence: 99%